Mineralocorticoid Receptor Antagonism Prevents the Synergistic Effect of Metabolic Challenge and Chronic Kidney Disease on Renal Fibrosis and Inflammation in Mice - Palacios-Ramirez, Roberto; Lima-Posada, Ixchel; Bonnard, Benjamin; Genty, Marie; Fernandez-Celis, Amaya; Hartleib-Geschwindner, Judith; Foufelle, Fabienne; Lopez-Andres, Natalia; Bamberg, Krister; Jaisser, Frederic (Frontiers in Physiology, 2022)
Obesity and/or metabolic diseases are frequently associated with chronic kidney disease and several factors associated with obesity may contribute to proteinuria and extracellular matrix production. Mineralocorticoid receptor antagonists have proven their efficacy in diabetic kidney disease with preclinical data suggesting that they may also be efficient in non-diabetic chronic kidney disease associated to metabolic diseases. In the present study we developed a novel mouse model combining severe nephron reduction and High Fat Diet challenge that led to chronic kidney disease with metabolic alterations. We showed that the MR antagonist canrenoate improved metabolic function, reduced albuminuria and prevented the synergistic effect of high fat diet on renal fibrosis and inflammation in chronic kidney disease mice.